Psammophilic scorpions in deserts of Iran - Navidpour SH (Global Journal of Zoology - Peertechz Publications, 2021)
In this study totally 3453 scorpions belonged buthidae family collected from different localities in south and southwestern provinces of Iran. The six psammophilic scorpions were identified in this research: Kraepelinia palpator, Polisius persicus, Apistobuthus susanae , Buthacus macrocentrus, Vachoniolus iranus and Compsobuthus jakesi.